NANOCIÊNCIA PARA O ENSINO DE FÍSICA NA EDUCAÇÃO DE JOVENS E ADULTOS NUMA ABORDAGEM CTS. - COSTA, Cassandra Maria Ribeiro (2019)
This study addresses a theme of contemporary science that was developed in physics classes, with third-year high school students, from the modality of Youth and Adult Education (EJA), in a public school in the municipality of São José de Ribamar, in the state of Maranhão. Initially, a Teaching Unit was elaborated as a methodological instrument to study the theme "nanometric particles" based on the approach of the Science Technology and Society (CTS) movement. Developed in five meetings, the study began with the application of two questionnaires with the purpose of tracing the profile of the subjects surveyed and obtaining previous knowledge of these subjects on the theme to be studied. In the following meetings, activities were carried out involving video screenings and readings of texts, followed by discussions and textual productions in answers to questions raised to raise reflection on the theme under discussion. After completing the activities in the school and analyzed the meanings of the students' productions, it was found that the study on Science/Physics and Technology on the nanometric scale produced reflections in students that point to the formation of critical positioning and social responsibility, subsidies that can lead those involved to a possible social transformation.